Psychological support of personality: methods and features of work of the clinical psychologist - Kihtyuk , Oksana; Fedotova , Tetiana (Psychological Prospects Journal, 2021)
The purpose of the article is to carry out a theoretical and methodological analysis of the concepts of psychological support, psychological assistance, psychological rehabilitation, first psychological assistance (PPD), psychological counseling. Empirically study the effectiveness of group work in the preventive activities of a clinical psychologist on the example of the introduction of socio-psychological training for the formation of communicative tolerance and nonviolent communication of the individual.Methods. Such methods of theoretical scientific research as analysis, synthesis, generalization and systematization of scientific sources on methods of work of the clinical psychologist, psychological help, support, rehabilitation of the person were used; observations, interviews, questionnaires and statistical elaboration of the obtained results before and after the implementation of the experimental program were carried out.The results. The main aspects of the professional activity of a clinical psychologist are presented. The importance of realization of the main tasks of activity and professional orientation of the clinical psychologist is proved: diagnostics, preventive educational work, psychoprophylaxis, the direction on rehabilitation, carrying out psychotherapy. Theoretical analysis of the concepts of psychological support, psychological assistance, psychological rehabilitation, first psychological assistance (PPD), psychological counseling, shows similarity and non-fundamental identity, focus on finding personal resources, adaptation to new situational life circumstances. The importance of PPD is described. The main modern methods of work of the clinical psychologist are allocated. The method of nonviolent communication is described, the peer-to-peer method. The effectiveness of psychological and psychotherapeutic support groups in the work of a clinical psychologist has been determined. Empirically, the effectiveness of socio-psychological training and shaping training, based on methods of nonviolent communication, the method of peer-to-peer.Conclusions. Conducting an experimental program in the form of socio-psychological training has shown the effectiveness of using an eclectic approach in the choice of psychotechnical methods for group work of a clinical psychologist. The introduction of such a plan of educational and developmental programs is psychological help and support for modern youth at the stage of becoming a mature person. We see the prospect of future research in the development and implementation of socio-psychological training in the work of a clinical psychologist, using an eclectic approach in the choice of psychotechnical exercises and methods of psychological impact on the individual.